Analysis of the External and Internal Environment at the Fire and Rescue Training Centre of DKI Jakarta Province - Djuanita, Maharani Kinanti; Zamzamiyatul, Eva (Universitas Muhammadiyah Jakarta, 2024)
Internal and external environmental analysis is a very important initial assessment step in business strategy design. This article examines the external and internal environment at the fire and rescue training center of DKI Jakarta province. The problem in this essay is investigated qualitatively, utilizing descriptive approaches. The data collection method employs triangulation, and data analysis is done inductively. The external environment was evaluated using the Political, Economic, Social, and Technology (PEST) method and Porter's Five Forces, whereas the internal environment was analyzed using the Resource-based View (RBV) approach and the value, rarity, imitability, and organization (VRIO) frameworks. The external environment was analyzed using the Political, Economic, Social, and Technology (PEST) approach and Porter's Five Forces, while the internal environment was analyzed using the Resource-based View (RBV) approach and the value, rarity, imitability, and organization (VRIO) frameworks. The results of the external analysis show that the competitive strength of the Fire Prevention and Suppression Training Centre of DKI Jakarta Province is in the medium category. According to the findings of the internal analysis, the resources and capabilities that give the company a competitive advantage are training buildings, certified instructors, the only government relations, and the ability to design training programs based on needs, while other aspects such as technology, supporting facilities, funding flexibility, excellent service, and forming business partnerships remain competitively parity.